Interictal Activity Is Associated With Slower Binocular Rivalry in Idiopathic Generalized Epilepsy - Wu, Jiaonan; Ding, Wei; Ye, Xing; Wei, Qiang; Lv, Xinyi; Tang, Qiqiang; Tian, Yanghua; Wang, Kai; Jiang, Yubao (Frontiers in Neurology, 2021)
Objective The perceptual alternations evoked by binocular rivalry (BR) reflect cortical dynamics strongly dependent on excitatory‒inhibitory balance, suggesting potential utility as a biomarker for epileptogenesis. Therefore, we investigated the characteristics of BR in patients with idiopathic generalized epilepsy (IGE) and the potential associations with clinical variables. Methods Sixty-two healthy controls (HCs) and 94 IGE patients completed a BR task. Perceptual alternation rates were compared between HC and IGE groups as well as among the HC group and IGE patients stratified according to presence or absence of interictal activity on ambulatory electroencephalogram (AEEG), termed the abnormal AEEG group (AB-AEEG, n = 64) and normal AEEG group (N-AEEG, n = 30), respectively. Results The IGE patients demonstrated a slower rate of BR perceptual alternation than HC subjects ( p < 0.001). The alternation rate also differed among the HC, AB-AEEG, and N-AEEG groups (p < 0.001), and post hoc comparisons indicated a significantly slower alternation rate in the AB-AEEG group compared with the N-AEEG and HC groups . Stepwise linear regression revealed positive correlations between the BR alternation rate and both the AEEG status (, 0.173; standard error, 0.022 p < 0.001) and Montreal Cognitive Assessment （MoCA） score (, 0.013; standard error, 0.004; p = 0.003). Receiver operating characteristic (ROC) curve analysis of the BR alternation rate distinguished AB-AEEG from N-AEEG subjects with 90.00% sensitivity and 76.90% specificity (area under the curve (AUC) = 0.881; 95% CI = 0.801− 0.961). Alternatively, MoCA score did not accurately distinguish AB-AEEG from N-AEEG subjects and the AUC value of the ROC curve combining the BR alternation rate and MoCA score was not markedly larger than that of BR alternation rate alone (0.894, 95% CI = 0.822 − 0.966, p < 0.001). Forward stepwise linear regression model demonstrated number of interictal epileptiform discharges (β, 0.001; standard error, 0.001; p = 0.025) as an independent factor associated with the BR alternation rate. Conclusion These results suggest that interictal epileptiform activity is associated with disruptions in perceptual awareness, and the BR may be a useful auxiliary behavioral task to diagnose and dynamically monitor IGE patients with interictal activity.